A systematic literature review of tourism translation and power - Lu, Rong; Abdullah, Muhammad Alif Redzuan; Ang, Lay Hoon; Abdul Ghani, Che An (Sciedu Press, 2023)
Despite many studies on translation and power, little has been done to examine the power relations in tourism translation. This systematic literature review aims to investigate publications on tourism translation and power in the translation field. With Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) as the framework, this study employed two primary journal databases in English and Chinese, namely Scopus and CNKI. Following an eight-step guide, a total of eight articles, including seven journals and one book chapter, were included in the final research. Based on systematic literature review and thematic analysis methods, four main themes were identified concerning the power issues in tourism translation. The first theme showed the subjective exertion of power by the translators in tourism translation to promote tourism in a destination. The second theme demonstrated the power exertion in translating tourism texts for economic reasons. The third and fourth themes referred to ideology-related and culture-related power exertion in the process of translating tourism texts. Apart from the emerging themes, the most notable study outcome indicated three research gaps in tourism translation and power, concerning language pairs, translation strategies, and research methodology.